Osler-Weber-Rendu Syndrome in association with port wine spot - Awan, Abdul Khalid; Baqai, Mohammad Mohammad Tariq; Bukhari, Murtaza (International Journal of Pathology, 2018)
AbstractOsler-Rendu-Weber syndrome also known as hereditary hemorrhagic telangectasiea (HHT) is anautosomal dominant vascular disorder. The pathogenesis of this disorder involves dilated postcapillaryvenules in the mucus membranes of different organs and large arteriovenous malformations.Gastrointestinal hemorrhages contribute to iron deficiency anemia in one third of these patients. Portwine stains belong to the family of arteriovenous disorders. These are due to abnormally dilatedcapillaries and produce reddish or pink discoloration of the skin. These are present at birth andincrease in size during the growth period. No association has so far been reported between port winestains and hereditary hemorrhagic telangectasiea. We report a case of 41 years old lady presenting withco- existence of these two lesions.